The Europeanization of heritage and memories in Poland and Sweden - Kowalski, Krzysztof; Törnquist Plewa, Barbara (Jagiellonian University Press, 2016)
This book attempts to describe and understand the processes which are at work in the Polish and Swedish contexts and lead to the construction of new, Europeanized representations of the past. It asks how the ongoing process of European political integration influences local, regional, national, and transnational interpretations of the past in these two countries. It is the outcome of a multidisciplinary effort on the part of Polish and Swedish researchers working in the fields of ethnology and cultural anthropology, the sociology of culture, history, memory, and heritage studies. It describes a variety of cases and approaches while at the same time being firmly anchored in shared research questions and the authors' common attempts to grasp the sometimes fluid and elusive aspects of the Europeanization of heritage and memories in Poland and Sweden. The selection of cases presents the diverse directions of the processes of Europeanization as well as its dynamics in places which differ in terms of their axiology. The contributors analyze its influence in places connected with contemporary museum narration (Lucja Piekarska-Duraj), transnational initiatives (Lars-Eric Jönsson), regional/transnational idylls (Eleonora Narvselius), national pride (Krzysztof Kowalski), dark memories from the period of the Second World War (Barbara Törnquist-Plewa, Björn Magnusson Staaf, Elisabeth Büttner) and new forms of heroism (Ulf Zander, Katarzyna Suszkiewicz). The examples of the Europeanization of heritage and memory provided in this volume show that its efficacy varies, with some places easily being linked to the European context and others resisting it. In other words, it does not follow the same course everywhere nor does it lead to the same redefinition of the past.--
Keywords: Karski, Jan; Wallenberg, Raoul; Euroopan neuvosto; Solidarność (ammattiliitto); Group identity : European Union countries; Social integration : Europe; Social integration : Poland; Social intergration : Sweden; Social values : Europe; Social values : Poland; Social values : Sweden; Collective memory : Europe; Collective memory : Poland; Collective memory : Sweden; Politics and culture; muistin politiikka; historiakulttuuri; EU-maat; Euroopan integraatio; kollektiivinen muisti; kulttuuriperintö; eurooppalaisuus; eurooppalaistuminen; museot; viikingit; toinen maailmansota; holokausti; muistomerkit; keskitysleirit; minnets politik; historiekultur; EU-länder; europeisk integration; kollektivt minne; kulturarv; europeisk identitet; europeisering; museer; vikingar; andra världskriget; holocaust; minnesmärken; koncentrationsläger; Eurooppa; Puola; Ruotsi; Europa; Polen; Sverige